2017
DOI: 10.1002/1873-3468.12910
|View full text |Cite
|
Sign up to set email alerts
|

The dual effects of the astrocyte‐specific enhancer of the AQP4 M1 promoter

Abstract: Aquaporin-4, a predominant water channel in the central nervous system, has two isoforms, M1 and M23, whose transcripts are driven by distinct promoters. Using a reporter assay, we found that a fragment located between exons 0 and 1 of the mouse aquaporin-4 gene, which had been thought to be the promoter for M23, lacked enhancers functioning in astrocytes. When the astrocyte-specific enhancer (ASE) of the M1 promoter is connected to the putative M23 core promoter, it also works in astrocytes. Importantly, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Our results show that increased AQP4 is accompanied by increased astrocytes and microvessels ( Figure 4 ). The role of these complex microenvironment changes in the pathogenesis of cerebral ischemia has not been fully elucidated, and the dual role of AQP4 relies on the proportion of subtypes and the change of molecular structure rather than the amount ( Barati Farimani et al, 2014 ; Abe et al, 2017 ; Lisjak et al, 2017 ; Palazzo et al, 2019 ; Simone et al, 2019 ). Sun et al (2022) recently showed that peri-infarct AQP4 polarization correlated positively with the ultra-high b -values of ADC in rat at 14 days after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that increased AQP4 is accompanied by increased astrocytes and microvessels ( Figure 4 ). The role of these complex microenvironment changes in the pathogenesis of cerebral ischemia has not been fully elucidated, and the dual role of AQP4 relies on the proportion of subtypes and the change of molecular structure rather than the amount ( Barati Farimani et al, 2014 ; Abe et al, 2017 ; Lisjak et al, 2017 ; Palazzo et al, 2019 ; Simone et al, 2019 ). Sun et al (2022) recently showed that peri-infarct AQP4 polarization correlated positively with the ultra-high b -values of ADC in rat at 14 days after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The role of membrane protein anchoring factors in the OAP assembly is strictly correlated to AQP4 isoform expression. In the natural context the expression pattern of the AQP4 gene in astrocytes includes at least three other isoforms, M1-AQP4 and two C-terminal extended isoforms named M1ex-AQP4 and M23ex-AQP4, generated by finely regulated alternative transcription/promoters [47] and translational control mechanisms [17,41]. The analysis of OAPs at the level of perivascular astrocyte processes has shown that AQP4 is co-expressed and co-localized with C-terminal extended isoforms.…”
Section: Discussionmentioning
confidence: 99%